2003
DOI: 10.1111/j.1749-0774.2003.tb00152.x
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive Immunotherapy of Cancer using Activated Autologous Lymphocytes -Current Status and New Strategies-

Abstract: After the discovery of interleukin-2 (IL-2), lymphokine-activated killer (LAK) cells, tumor-infiltrating lymphocytes (TILs), and cytotoxic T lymphocytes (CTLs) sensitized with the mixed lymphocyte-tumor culture (MLTC) system have been conducted in adoptive immunotherapy (AIT) trials during past 15 years. Although the overall response rate of tumor shrinkage was marginal (9%), locoregional administration of TILs for malignant effusions was effective (77%) for a decrease or disappearance of the effusions even in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…It has been reported that IL-2-activated peripheral blood LAK cells consist of CD4 + and CD8 cells as well as NK cells (26,27). Moreover, we have system for easily expanding LAK cells in our laboratory (13). Our preliminary clinical investigation showed that postoperative LAK cell transfer restores the decrease in helper and cytotoxic T-cell populations.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…It has been reported that IL-2-activated peripheral blood LAK cells consist of CD4 + and CD8 cells as well as NK cells (26,27). Moreover, we have system for easily expanding LAK cells in our laboratory (13). Our preliminary clinical investigation showed that postoperative LAK cell transfer restores the decrease in helper and cytotoxic T-cell populations.…”
Section: Discussionmentioning
confidence: 75%
“…We have carried out ex vivo cell therapy for cancer treatment using activated autologous lymphocytes, including lymphokine-activated killer (LAK) cells, tumor-infiltrating lymphocytes (TILs), and tumor-sensitized lymphocytes, but tumor responses are limited with regard to quality of life in locoregional administration for malignant effusion from gastrointestinal cancers (13). Ueda et al have reported an efficacy of AIT using LAK cells for metastatic esophageal cancer (14).…”
Section: Introductionmentioning
confidence: 99%
“…19,20,30 Many attempts have been made to improve the functions of adoptively transferred cells, for instance, Toh et al, activated tumor infiltrated lymphocytes in vitro by using IL-2 to optimize immunotherapy against tumor. 31 Burger et al, re-stimulated TILs with autologous irradiated tumor cells in vitro to enhance the specificity of TILs transferred into tumor-bearing mice.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] In the past decades, adoptive cell transfer (ACT) immunotherapy developed into an important therapeutic strategy against tumors. 19,20 Tumor infiltrating lymphocytes (TILs), isolated from the tumor and expanded in vitro were considered as the best candidate for ACT because of their directed interaction with tumor cells and ability to become antigen-specific lymphocytes. 21,22 However, the efficacy of adoptive transfer of TILs is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Cytokine-induced killer (CIK) cells are a type of common antitumor immunocompetent cells. They exhibit strong proliferation capacity and high antitumor activity in vitro, and they are particularly effective against multidrug-resistant tumor cells (Yamaguchi et al, 2003). Previous studies have shown that when DCs are cocultured with CIK cells in vitro, they can promote the proliferation of CIK cells and enhance their cytotoxic effects against tumor cells (Marten et al, 2001b).…”
Section: Introductionmentioning
confidence: 99%